Determinación de la presencia de hemotrópicos (babesia spp, ehrlichia canis y anaplasma spp) en caninos del cantón Catamayo. - Ruiz Cabrera, Cristina Lisbeth (2021)
Hemotropic are microscopic agents that live and reproduce in the circulatory system, outside or inside red or white blood cells. The diseases that produce are of great importance both for the impact generated on animal health, and for the problems that it can cause in human health, being considered to such an extent a threat to public health, being considered a threat to public health. The main objective of this research work was to determine the prevalence of Hemotropic in canines of the Canton of Catamayo, for this, a study of 115 canine patients, attended at the Veterinary Dogtor, with symptomatology to the disease. Diff Quick Staining® technique was used, obtaining 47 positive cases for B. canis (40,9%), 50 positive cases for E. canis (43,5%) and 30 positive cases of Anaplasma spp (26,1%); through the Cani Rapid Test V-4test Kit ®, 55 positive canines were obtained for Ehrlichia canis (47,8%) and 47 positive patients in case of Anaplasma spp (40,9%). When evaluating risk factors, only sex was statistically significant (p = 0.043). Keywords: Quick test, staining, cytology, Diff Quick®, Babesia spp, Ehrlichia canis, Anaplasma spp.